2022
DOI: 10.5194/acp-22-5515-2022
|View full text |Cite
|
Sign up to set email alerts
|

Offline analysis of the chemical composition and hygroscopicity of submicrometer aerosol at an Asian outflow receptor site and comparison with online measurements

Abstract: Abstract. Filter-based offline analysis of atmospheric aerosol hygroscopicity coupled to composition analysis provides information complementary to that obtained from online analysis. However, its application itself and comparison to online analysis have remained limited to date. In this study, daily submicrometer aerosol particles (PM0.95, 50 % cutoff diameter 0.95 µm) were collected onto quartz fiber filters on Okinawa Island, a receptor of East Asian outflow, in the autumn of 2015. The chemical composition … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 83 publications
2
4
0
Order By: Relevance
“…It is revealed that κ modulates CDSD (i.e., growth of cloud droplets) from the initial mixing state to the well‐mixed state in conjunction with two modes of aerosols. The numerical simulations propose that hygroscopicity of aerosol particles in the accumulation mode might be more important (Figure 4b,d), which is similar to results from a recent study by Deng et al (2022). The hygroscopicity indicates the activation of smaller droplets, which may help for invigorating the cloud by uplifting below the freezing level due to a strong updraft, influencing the rain intensity.…”
Section: Resultssupporting
confidence: 87%
“…It is revealed that κ modulates CDSD (i.e., growth of cloud droplets) from the initial mixing state to the well‐mixed state in conjunction with two modes of aerosols. The numerical simulations propose that hygroscopicity of aerosol particles in the accumulation mode might be more important (Figure 4b,d), which is similar to results from a recent study by Deng et al (2022). The hygroscopicity indicates the activation of smaller droplets, which may help for invigorating the cloud by uplifting below the freezing level due to a strong updraft, influencing the rain intensity.…”
Section: Resultssupporting
confidence: 87%
“…manuscript submitted to Journal of Geophysical Research-Atmosphere clearly propose that the hygroscopicity of aerosol particles in the accumulation mode might be more important (Fig.4b,d), which is similar to the recent study byDeng et al (2022). The results from numerical simulations with hygroscopicity indicate the activation of smaller droplets, which may help for the cloud invigoration by uplifting below freezing level due to strong updraft and influence rain intensity.…”
supporting
confidence: 87%
“…The calibrated RH values were 81 ± 0.15, 87 ± 0.25, and 94 ± 0.18% for the set of mosquito coil samples and 82 ± 0.17, 88 ± 0.26, and 93 ± 0.22% for the set of tropical peat samples. Further details about HTDMA are presented by Deng et al…”
Section: Methodsmentioning
confidence: 99%
“…The generated particles passed through two diffusion dryers filled with activated charcoal (granular 6–10 mm, Wako Pure Chemical Industries) and silica gel for removing the remaining solvents (methanol and 1-octanol) in the particles. The particles were introduced to the high-resolution time-of-flight aerosol mass spectrometer (HR-ToF-AMS, Aerodyne Research), hygroscopicity tandem differential mobility analyzer (HTDMA), , and cloud condensation nuclei counter (CCNC, Droplet Measurement Technologies) for further analyses (Figure S3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation